Factors of Interdepartmental Collaboration:A Field Study - Kong, Mun Meng (2011)
This dissertation hypothesises and analyses the impact of various ‘drivers’ and ‘facilitators’ of collaboration. It is different to the existing literature in that it segments different levels of stakeholders, geographically (to reflect cultural differences) and occupationally (to reflect differences in job roles). Furthermore, it proposes a framework for ushering in the desired traits of collaboration. Essentially, the message of this dissertation is clear: to drive collaboration,organizations must take the initiative to act and not leave it to chance.